2015
DOI: 10.1111/tpj.12863
|View full text |Cite
|
Sign up to set email alerts
|

An autophosphorylation site database for leucine‐rich repeat receptor‐like kinases in Arabidopsis thaliana

Abstract: SUMMARYLeucine-rich repeat receptor-like kinases (LRR RLKs) form a large family of plant signaling proteins consisting of an extracellular domain connected by a single-pass transmembrane sequence to a cytoplasmic kinase domain. Autophosphorylation on specific Ser and/or Thr residues in the cytoplasmic domain is often critical for the activation of several LRR RLK family members with proven functional roles in plant growth regulation, morphogenesis, disease resistance, and stress responses. While identification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 62 publications
1
36
0
Order By: Relevance
“…Similarly, alignment of the EMS1-CD with its most related LRR-RLKs (BRI1, BRL1, BRL2, and BRL3) shows that only the Ser-892, Thr-914, and Ser-1076 phosphorylation sites are conserved, but nine other phosphorylation sites are diverse (Supplemental Fig. S7; Wang et al, 2005Wang et al, , 2008Mitra et al, 2015). Our studies showed that the S1076A mutation reduced 65% of EMS1 autophosphorylation activity.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…Similarly, alignment of the EMS1-CD with its most related LRR-RLKs (BRI1, BRL1, BRL2, and BRL3) shows that only the Ser-892, Thr-914, and Ser-1076 phosphorylation sites are conserved, but nine other phosphorylation sites are diverse (Supplemental Fig. S7; Wang et al, 2005Wang et al, , 2008Mitra et al, 2015). Our studies showed that the S1076A mutation reduced 65% of EMS1 autophosphorylation activity.…”
Section: Discussionsupporting
confidence: 51%
“…Furthermore, among 24 in vitro-identified phosphorylation sites in SERK1, only three sites are due to bacterial transphosphorylation (Karlova et al, 2009). A recent study reported the identification of in vitro autophosphorylation sites in 73 LRR-RLKs, including SERK1 but not EMS1 (Mitra et al, 2015). In this study, we identified five in vitro Ser and Thr phosphorylation sites in the EMS1 inner juxtamembrane domain and six in vitro Ser and Thr phosphorylation sites in the EMS1 ATP-binding domain and activation loop.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…The fourth phosphosite of MtLYR3 (Ser399) is located just after the predicted aC-helix, which is a key structural element in the N-terminal lobe of protein kinases [42]. The fifth phosphosite (Thr628) is located in the C-terminal domain of the protein, a region commonly subjected to phosphorylation [43], including in vivo for MtLYR4 and the Arabidopsis LRR-RLK, AtBRI1 [35,44]. Taken together, the phosphorylation of MtLYR3 by MtLYK3 revealed the existence of phosphosites that could be of relevance in a biological context.…”
Section: Discussionmentioning
confidence: 99%
“…To identify kinase(s) that phosphorylate a tyrosine residue on AtGPA1, we purified 70 recombinant LRR RLKs, containing the intracellular juxtamembrane, the catalytic kinase and the C-terminal domains (48). We biochemically screened these kinases for AtGPA1 substrate specificity ( Fig.…”
Section: Identification Of 18 Atgpa1 Kinases One Requires Y166 For Amentioning
confidence: 99%